(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The use of index numbers of species specially selected pairs of families (Pottiaceae / Amblystegiaceae, Bryopsida) Ind P / A to reflect the characteristics and features and certain changes in the ecological and geographical aspects Bryoflora geographical zones plains of Ukraine: the zone of mixed coniferous-deciduous forests (Ukrainian Polessye ), broadleaved forest zone (zone immoral), forest-steppe and steppe zones is characterized. the index has its highest value in bryoflora of steppe zone – 3.00 (at a ratio of the number of species families Pottiaceae / Amblystegiaceae 48/16 and size ombrorezhima 10,0–10,5 points). In the direction from south to north index value decreases regularly: in the forest-steppe zone – 2.21 (at a ratio of the number of species families Pottiaceae / Amblystegiaceae 51/23 and size ombrorezhimua 11.5–12.0 points) in the deciduous forest zone – 1, 81 (at the ratio of the number of species families Pottiaceae / Amblystegiaceae 59/32 and size ombrorezhimu 12.0 points) and in the zone of mixed coniferous-deciduous forests – 1.03 (at a ratio of the number of species families Pottiaceae / Amblystegiaceae 32/31 and size 12 ombrorezhimu 0–12.5 points). Also the analyzes of the value of families’ index pairs (Ind P / A) for all bryoflora phytogeographical regions of Ukraine is given. Index (ratio) species abundance of specially selected families reflects the zonal character of plain bryoflora and can be used in their typification, in allocating bryoflora to a certain type.